Terrestrial Snails (Mollusca: Gastropoda) as Intermediate Hosts of Protostrongylid Nematodes in Balkan Chamois in the Regions of Western Rhodopes Mts and Pirin Mts., Bulgaria: Preliminary Data - Yanko G. Yankov (Ecologia Balkanica, 2018)
The nematodes from family Protostrongylidae Leiper, 1926 parasitize in the lungs of wild and domestic ruminants and rabbits. Five meadows from the region of Western Rhodopes Mts and Pirin Mts used from the Balkan chamois (Rupicapra rupicapra balcanica) were studied for terrestrial gastropods as a potential intermediate hosts of protostrongylids, during the summer of 2018. A total of 28 specimens of Cattania haberhaueri, Xerolenta macedonica and Helix pomatia in the Pirin Mts and 161 specimens of Zebrina detrita, Chondrus zebra tantalus, Xerolenta sp., Cattania rumelica, Cepaea vindobonensis and Euomphalia strigella in the Western Rhodopes Mts were collected. The highest levels of infestation with protostrongylids were detected in Xerolenta macedonica and Xerolenta sp. for the meadows of Pirin Mts and Western Rhodopes Mts, respectively.